LITERATURE REVIEW: “IMPLEMENTATION OF ALLOWANCE FOR IMPAIRMENT LOSS RESERVES BASED ON PSAK 71 IN FINANCIAL INSTITUTIONS” - Abdulloh Sayyid Addu; Muhammad Hariz (Department of Accounting, Faculty of Economics, Universitas Nurtanio Bandung, 2024)
The aims of this research is to determine the implementation of impairment loss reserves based on PSAK 71 in financial institutions using secondary data from 11 previous journals. This research used qualitative approach with literature review method. Result of a reseach is there are several important found in this research. Analysis of 11 journal publications related to the implementation of impairment loss reserves based on PSAK 71 in financial institutions from 2020-2024 is as follows:First, mostly methods used by previous journal were qualitative approach using secondary data, some of which were sourced from the IDX website and interviews to answer phenomena related to the implementation of impairment loss reserves based on PSAK 71 in financial institutions, amounted 9 (82%) of 11 journals obtained. Meanwhile, quantitative approach used,amounted 2 (18%) of 11 journals obtained. Second, object of research conducted in previous research related to the implementation of impairment loss reserves based on PSAK 71 was dominated by bank financial institutions amounted 8 (73%) journals obtained. Meanwhile, non-bank institutions amounted 3 (27%) journals obtained. Third, based on the journals found by the authors based the object of previous research, there are 9 (82%) journals obtained that implemented PSAK 71. Meanwhile, there are 2 (18%) journals obtained that do not implemented PSAK 71. The implementation of PSAK 71 has been widely adopted by many entities. This indicates a significant trendtowards compliance with the accounting standard, reflecting the importance placed on adhering to regulatory requirements within the financial reporting landscape.